Transitional urban enslave: an arrival space for rural-urban migrants in Windhoek, Namibia - Besser, Carmen (University of the Free State, 2019)
This dissertation stemmed from an interest in the homeless living within the city of Windhoek. Most homeless individuals in the city are rural-urban migrants; therefore an investigation into the creation of an architectural typology to counter the gap that exists between arrival and settlement within the city. Cities are places of opportunity. People move from rural to urban areas for better socio economic conditions. Windhoek, being the hub of prospect in Namibia is a magnet for migrants. Though once individuals arrive, some experience immediate feelings of displacement and isolation, due to a lack of skills, education, income and security. They struggle to find employment, which adds to the unemployment statistics. This leads to some resorting to crime, alcohol, drug abuse or ending up homeless. Due to the constant pull factors migration is an incessant practice, rendering urbanization timeless. Therefore this research document intends to counter this inclination through preparedness. It explores how architecture can be a catalyst which can receive, prepare, house and release migrants into the city. The delimitation of the study is to avoid being “another homeless Centre”, but instead a liminal space between opportunist and opportunity. The site is situated within the dynamic Independence Avenue within the CBD of Windhoek, Namibia.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2019
Keywords: Rural-urban migrants - Windhoek; Urbanization - Windhoek; Economic factors - Windhoek; Poverty - Crime - Alcohol abuse - Windhoek